KONTRIBUSI CORPORATE SOCIAL RESPONSIBILITY (CSR) PT TIMAH PADA MASYARAKAT DI PRAYUN KECAMATAN KUNDUR UTARA KABUPATEN KARIMUN PROVINSI KEPULAUAN RIAU - Norliza Avera; Isjoni '; Bunari ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Corporate Social Responsibility (CSR) is the contribution of a company focused on business activities, social investment and philanthropy programs and public obligations. In addition CSr is also a commitment of a company to account for the impact of operations in social, economic and environmental dimensions. PT. Timah is a state-owned enterprise unit engaged in mining of Timah. From 1953-2015 PT. Tin is constantly changing. PT. Tin in Prayun Village early production through land mine, with land clearing in 1970. PT. Tin (Persero) Company engaged in mining both on land and sea. The purpose of this study is to determine the contribution of Corporate Social Responsibility (CSR) PT. Tin to the community in Prayun District Kundur Utara Karimun District Riau Islands Province. The method used is historical method where data collected through observation, interview, documentation, and literature study. Data analysis using historical writing method. The time of study started from the submission of the title of the proposal until the completion of the writer's thesis. The results show that the Community Development Program (CSR) is a movement designed to improve the livelihoods of weak economic communities through the development of community support and initiatives that are supportive. In implementing the CSR program the role of government and private or other related institutions are important elements that must be considered. The community provided should also be involved in planning and implementation peroses. .Keywords: CSR, PT. Tin, Contribution, Prayun Village